ANALISIS KONTEN EDUKASI KESETARAAN GENDER DARI PERSPEKTIF LAKI-LAKI (Studi Deskriptif pada Media Sosial di Instagram @lakilakibaru) - Aditya Hamdani (2023)
This study aims to discuss gender equality education from a male perspective which is discussed by the Aliansi Laki-laki Baru on Instagram @lakilakibaru. Agenda-setting theory is used to select the content that has a gender equality perspective. This type of research is descriptive qualitative with the method used namely content analysis using primary data sources from documented materials through Instagram content @lakilakibaru and source triangulation by conducting interview validation. Secondary data is in the form of journals, literature reviews, previous research, and other articles that have similarities with the thesis topic. Data retrieval techniques are collected through selected content on research objects determined according to certain criteria. The stages of data analysis use the Miles and Huberman concept which consists of data reduction, data presentation, and conclusions. The final results of this study show that the Aliansi Laki-laki Baru communicates gender equality educational content through simple approaches such as content regarding family relationships in an equal way of parenting, the impact of toxic masculinity, and calls men to fight sexual violence.